2020
DOI: 10.7150/ijms.42654
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as potential biomarkers for the progression of gastric cancer inhibit CREBZF and regulate migration of gastric adenocarcinoma cells

Abstract: In our previous study, we identified three miRNAs (hsa-miR-421, hsa-miR-29b-1-5p, and hsa-miR-27b-5p) with two mRNAs (FBXO11 and CREBZF) that might play an important role in the development of gastric adenocarcinoma (GAC) from premalignant adenomas. However, the expression and function of these miRNAs have not been not well characterized. We investigated the roles of CREBZF and miRNAs as potential biomarkers for the progression of gastric cancer (GC) in low-/high-grade dysplasia and early gastric cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Additionally, another study examining a total of 2573 patients also suggested that overexpression of miR-92a serves as an unfavorable prognostic indicator in LUAD patients [35]. To our knowledge, miR-27b-5p had been reported as a tumor suppressor in ovarian carcinoma and oral cancer [20,36], but it is highly expressed in gastric adenocarcinoma and may play a positive role in tumorigenesis and development [37]. However, regrettably, no study has reported the relationship between Evidence-Based Complementary and Alternative Medicine miR-27b-5p and lung cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, another study examining a total of 2573 patients also suggested that overexpression of miR-92a serves as an unfavorable prognostic indicator in LUAD patients [35]. To our knowledge, miR-27b-5p had been reported as a tumor suppressor in ovarian carcinoma and oral cancer [20,36], but it is highly expressed in gastric adenocarcinoma and may play a positive role in tumorigenesis and development [37]. However, regrettably, no study has reported the relationship between Evidence-Based Complementary and Alternative Medicine miR-27b-5p and lung cancer.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, bioinformatics analysis and luciferase reporter assay proved that miR-29b-1-5p was the downstream target of HOTAIRM1. Kim et al demonstrated that miR-29b-1-5p, acting as a GC development promoter, regulated GC cell migration by targeting CREBZF (Kim et al 2020). Additionally, it has been reported that the lower expression of miR-29b-1-5p reduced the IC50 of human breast cancer parental cell line MCF-7 selected at 500 nM Adriamycin, and the higher expression of miR-29b-1-5p weakened the effects of liposomal curcumin to Adriamycin-resistance (Zhou et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gene FBXO11 , XPO1 , SLC3A2 , and APC , whose mutation detections may be affected by various tumor purities in gastric cancer, were closely related with cancer occurrence and development. For examples, protein FBXO11 has both the E3 ubiquitin ligase and methyltrasferase activity, which could facilitate epithelial-mesenchymal transition (EMT), promote PI3K/AKT pathway activation, and regulate metastasis and apoptosis in human cancer ( Kim et al, 2018 , 2020 ; Sun et al, 2018 ). Protein XPO1 is positively correlated with cell proliferation and growth transformation, and negatively correlated with poor survival outcomes, which could be a promising molecular target in gastric cancer ( Subhash et al, 2018 ; Gruffaz et al, 2019 ; Sexton et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%